O conceito de “Igreja em saída” como princípio hermenêutico do pensamento do Papa Francisco - Dantas, José Erivaldo (2019)
This dissertation seeks to understand the concept of the "Church which goes forth" as the hermeneutical principle of the thinking of Pope Francis, who since his election on March 13, 2013 has firmly expressed the Church's desire for renewal in order to transform a Church self-referential in a decidedly missionary Church, attentive to the "signs of the times". The bibliographical research was used as a working method, considering the discourses, exhortations, homilies and encyclicals of the Pope Francisco, as well as works of relevant authors that somehow treat, specifically of the pontificate of Francisco or of some specific subject in the ecclesial perspective. From the analysis of this material, an attempt was made to respond to the problems raised, in order to defend the hypothesis that the concept of "Church which goes forth" is related to the rehabilitation of the concept of "People of God" at the center of the ecclesiology of the Catholic Church. In this sense, we sought to outline the current ecclesial scenario, starting with the Second Vatican Council, and the reflection of this event on the life and mission of Pope Francis, the principal authority of the Catholic Church, charged with carrying out the conciliar intuitions on the bias of a process of aggiornamento of the Church in the current ecclesial conjuncture